The Inherent Limitations of Gender-Based Violence to the Exclusion of LGBTIQ: A Guide for Social Workers - Leburu, Goitseone Emelda; Kgadima, Nathaniel Phuti; Malesa, Kgashane Johannes (International Journal of Criminology and Sociology, 2022)
Drawing from the queer theory, this article strives to understand the scourge of gender-based violence against members of the homosexual community through a literature review. There is a gap in understanding this scourge against LGBTIQ. Additionally, there is a dearth of research on GBV within the social work fraternity despite the profession’s mandate to protect vulnerable groups. A comprehensive understanding of this hate crime is critically important in the current times where incidents of violence based on one’s gender are on the rise in South Africa. Social workers are in a privileged position to educate communities about these appalling crimes and to inform inclusive policies to curb this pandemic against members of the homosexual community.